Dynamic range of cameras in photography - Nur Insyirah Binte Sulaiman (Nanyang Technological University, 2023)
Cameras cannot capture a single image as good as the eye may see. The human eye can respond to a wide range of light intensities, although not instantaneous, as opposed to a camera whose limited response relies on solid-state image sensors such as charged-coupled devices (CCD) and complementary metal-oxide semiconductors (CMOS).